Prospects of Developing Municipal Structures in the 21st Century (Illustrated by the Republic of Armenia) - G. K. Martirosyan; A. A. Avetyan (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
Nowadays many democratic states face the acute problem of even and sustainable regional development. The article studies different trends of organizational changes in the development of local self-governance in connection with social and economic changes. It is found out that the key hindrances for effective development of local selfgovernance are the standard of living of the population, the resource potential, investment appeal, the scale of local self-governance authority, the level of municipal facility infrastructure and low use of informational and advanced technologies in municipal services being rendered. In this aspect we focus on the issue of upgrading the system of strategic management of municipal structures’ development, which could provide an opportunity of identifying their promising directions and with the help of advanced information technologies reach a new level of development. The authors by analyzing academic data, key parameters of development and legislative and organizational principles of local self-governance in the Republic of Armenia prepared recommendations aimed at modernizing the system of municipal structures’ management, which would allow us to build an efficient, flexible and economical system of local self-governance. Findings of the research could be used both in the system of state and municipal governance and in academic research in the field of local self-governance development.